Disease burden of rotavirus gastroenteritis in children residing in Germany: a retrospective, hospital-based surveillance - Kowalzik, Frank; Tenenbaum, Tobias (The pediatric infectious disease journal, 2016)
Background: Representative, population-based epidemiologic data for gastroenteritis caused by rotavirus (RV) are rare. RV vaccines were first licensed in Europe in 2006 and recommended in 5 western federal states in 2008 or thereafter. This study establishes a baseline for assessing the impact of vaccination and delineates the RV disease burden in Germany today., Methods: Nationwide data obtained from hospitals for children 0 to 10 years of age and transferred to the Federal Statistical Office were analyzed retrospectively. Acute gastroenteritis cases because of RV were identified by the International Classification of Diseases code (ICD-10) combined with the referring diagnosis-related group code. Coding quality was validated by random sampling the patient records (n=1003). Crude and age-standardized rates per 100,000 person-years were calculated. The rate ratios of seasonal effects and recommended immunization adjusted for year, federal state and age were estimated using Poisson regression., Results: Between 2005 and 2010, 5,843,730 children were hospitalized; 520,606 cases were hospitalized because of acute gastroenteritis. RV caused 152,636 of these cases or an age-standardized rate of 302 hospitalizations per 100,000 person-years. Rates were slightly higher in boys than girls, decreased with age, and differed by federal state, year and season. Rate ratios decreased in those western federal states that recommended immunization and were inversely associated with vaccine doses sold., Conclusions: With an average of 25,440 children hospitalized yearly, RV infection has a great impact on the German healthcare system. Our findings indicate that RV immunization will lead to a decline in in-patient treatment and associated costs.